Globalisation and female economic participation in Sub-Saharan Africa - Simplice Asongu; Uchenna Rapuluchukwu Efobi; Belmondo V. Tanankem; Evans Osabuohien (African Governance and Development Institute (AGDI), 2019)
This study assesses the relationship between globalisation and the economic participation of women (EPW) in 47 Sub-Saharan African countries for the period 1990-2013. EPW is measured with the female labour force participation and employment rates. The empirical evidence is based on Panel-corrected Standard Errors and Fixed Effects regressions. The findings show that the positive effect of the overall globalisation index on EPW is dampened by its political component and driven by its economic and social components, with a higher positive magnitude from the former or economic globalisation. For the most part, the findings are robust to the control for several structural and institutional characteristics. An extended analysis by unbundling globalisation shows that the positive incidence of social globalisation is driven by information flow (compared to personal contact and cultural proximity) while the positive effect of economic globalisation is driven by actual flows (relative to restrictions). Pol icy implications are discussed with some emphasis on how to elevate women's social status and potentially reduce their victimisation to male dominance.
Keywords: E60; F40; F59; D60; O55; 330; Globalisation; female; gender; inequality; inclusive development; labour force participation; Africa